«National Project «Health»: Life-Saving Technologies in Cardiovascular Prevention and Treatment» (IV All-Russian Conference on Preventive Cardiology Tumen, November 8-10 2006) - S. V. Shalaev (Кардиоваскулярная терапия и профилактика)
.